A reliable initial rotor position estimation method for sensorless control of interior permanent magnet synchronous motors. (February 2020) - Wu, Xuan; Huang, Sheng; Liu, Ping; Wu, Ting; He, Yunze; Zhang, Xiaofei; Chen, Kun; Wu, Qiuwei
Abstract: In this paper, a novel initial rotor position estimation method for reliable start-up of the IPMSM is presented. The proposed method combines the improved high frequency pulse signal injection with positive and negative d -axis current bias injection. Differing from the conventional initial rotor position detection scheme, the injection and the field-oriented control periods are separated in the proposed method. Therefore, the filters are not needed in the process of high-frequency response current and fundamental current extraction. The magnet polarity can be estimated by exciting the positive and negative d -axis currents. Afterwards, the peak values of d -axis current during the voltage injection period are accumulated to detect the rotor magnetic polarity. The proposed method can improve the reliability of the magnet polarity detection. Moreover, it is suitable for both the standstill rotor application and the free-running rotor application. The effectiveness of the proposed method is verified on a 1.5 kW IPMSM drive platform. Highlights: A reliable initial rotor position detection method for sensorless control of the IPMSM is presented. No filters are needed for extracting the fundamental currents and the induced currents. The proposed method can improve the reliability of magnet polarity detection. The proposed method is suitable for standstill rotor application and free-running rotor application.